The Interval Parameter Optimization Model Based on Three-Way Decision Space and Its Application on “Green Products Recommendation” - Mingxia Li; Kebing Chen; Caiyun Liu; Baoxiang Liu (Discrete Dynamics in Nature and Society)
The interval concept lattice theory, a new method of mining objects based on interval parameters, can more accurately deal with uncertain information than the classical concept lattice theory. The optimization of interval parameters has been a problem that is not well solved. From the perspective of three-way decision space, we first combine the theories of interval concept lattice and three-way decision and then put forward interval three-way decision space theory; second, in the interval three-way decision space, the positive region, negative region, and boundary region are divided by extension of interval three-way decision concept; further, the decision loss function and three-way decision rules are extracted. Through adjusting interval parameters of the lattice structure, we could find that when parameter α is roughly 0.6, more credible decision rules will be mined and decision-making becomes more clear than that under the condition α is less than 0.6; finally, we verify the model by a “Green Products Recommendation” example.